An open-source OpenSim® ankle-foot musculoskeletal model for assessment of strains and forces in dense connective tissues. (September 2022) - Sikidar, Arnab; Kalyanasundaram, Dinesh
Highlights: An extended musculoskeletal model of ankle joint-foot complex was developed. The model incorporates 24 DOFs constituting 13 rigid bodies and 161 soft tissues. CT and MRI data were used to segment the bones and attachment sites of soft tissues. Forward simulation was carried out for each DOF in the model within the range of motion. Strain, ISR and force developed in the ligaments were recorded and analysed. Abstract: Background: The ankle and foot are among the most critical load-bearing joints in the human anatomy. Anatomically accurate human body models are imperative to understanding the mechanics of injury and musculoskeletal disorders. A typical human ankle-foot anatomy consists of 25 DOFs, 112 dense connective tissues (DCTs) (92 ligaments, one capsule and 19 fasciae), 30 tendons, and 65 muscles. Existing models possess less than half of the DOFs and physiological elements. In this work, we have developed an ankle-foot joint complex musculoskeletal model for the OpenSim® platform by incorporating 24 degrees of freedom (DOF) comprising of 66 DCTs (46 ligaments, one 1 capsule and 19 fasciae), 30 tendons, and 65 muscles. Methods: Computed tomography (CT) data of human ankle joint-foot complex was segmented using Mimics ® (Version 17.0, Materialise, Belgium) to obtain models of the cartilages and bones of the ankle joint-foot complex. The position and resting lengths of the DCTs were attained from the MRI data and literature. Five joints, namely, tibiotalar, subtalar, chopart, tarsometatarsal (TMT), and metatarsophalangeal (MTP) joints and their joint axes were formulated to yield 24 DOFs. A forward simulation was carried out at each joint of the ankle-foot complex within their respective range of motions. The strains, instantaneous strain rates, and forces developed in the ligaments during the simulation were studied. Results: During plantar-dorsiflexion of the tibiotalar joint, the anterior tibio-talar ligament (aTTL) yielded the maximum strain compared to all other ligaments. Anterior tibio-fibular ligament (aTFL) experienced extreme strain during subtalar inversion. Hence, the coupled kinematics of subtalar inversion and plantar flexion are failure-prone activities for aTFL. The chopart, TMT, and MTP joints yielded maximum strains or forces for several bundles at the extremes of the range of motion. This signifies that rotations of these joints to their extreme range of motion are prone to failure for the bundles attached to the joint complex. Conclusion: The results illustrate the potential application of the proposed OpenSim® ankle-foot model in understanding the ligament injury mechanism during sports activity and its prevention. Researchers can use the proposed model or customise it to study complex kinematics, understanding injury mechanisms, testing fixtures, orthosis or prosthesis, and many more in the domain of musculoskeletal research.